Resistance Training as a Candidate Intervention for Aromatase Inhibitor Adherence in Postmenopausal Breast Cancer Survivors: A Narrative Review of Musculoskeletal Outcomes and Adherence Pathway - Aleksandrowicz, Katarzyna; Woźniak, Aleksandra; Król, Matylda; Meszka, Mateusz; Mamach, Anna; Straszewska, Aleksandra; Sobantka, Patrycja; Grygorczuk, Oliwia; Grodzka, Zofia; Mokrzecki, Szymon; Brzezińska, Karolina (Quality in Sport, 2026)
The use of adjuvant aromatase inhibitor (AI) therapy decreases recurrence in postmenopausal hormone receptor-positive breast cancer. Survival benefit depends on patients’ compliance to the prescribed course. Up to 85.9% of women report AI-induced musculoskeletal symptoms (AIMSS). In the CANTO cohort AIMSS independently predicted noncompliance (aOR 2.35, 95% CI 1.51–3.64). This narrative review analysed evidence on resistance training (RT) in postmenopausal AI-treated survivors putting an emphasis on the patients’ compliance to proposed treatment.Two cohorts meeting strict inclusion criteria - the HOPE trial and the de Paulo group - together with two boundary cohorts, converge directionally. RT alleviate AIMSS severity, improves body composition, improves quality of life, and is safe to apply to everyday life. In HOPE resistance training combined with aerobic training reduced the worst experienced pain by a 1.8 point (95% CI 0.9–2.6; p<0.001), exceeding the minimal difference which is important clinically. Cochrane GRADE rates the overall evidence as very low. Proposed mechanisms remain biologically plausible but untested in AI-treated survivors.No completed trial has used AI compliance as a primary outcome. The REJOIN trial is yet to be pending. We propose a hypothesis-generating operational prescription - three sessions per week with progressive loading at 55-75% one-repetition maximum, impact components, supervised delivery, minimum nine months - as a target for confirmatory trials with adherence as the primary endpoint.